Identification system for detecting and suppressing unmanned aerial vehicles based on video interception for use in combat conditions - A. A. Konik; R. E. Afonin; I. M. Klimov; D. S. Zinchenko (Российский технологический журнал)
Objectives. In the context ofmilitary operations, states face the threats of attacks by unmanned aerial vehicles (UAVs) on vulnerable assets, in particular, those pertaining to law enforcement agencies. Currently, there is no uniform or— more importantly—effective approach to detecting and suppressing certain types of UAVs, in particular, first person view (FPV) drones. The aim of the work is to develop modernized systems for the detection and suppression of enemy unmanned aerial vehicles and to justify their full-scale implementation in the service activities of law enforcement agencies.Methods. The work used system-structural, comparative-legal, and measurement research methods along with analysis, observation, and field modeling. In addition, the research refers to generalized and systematized experience of using UAVs in combat conditions.Results. The structure, basic tactical and technical characteristics are described according to the principle of operation of the identification complex for detecting and suppressing UAVs, having the ability to intercept analog radio signals carrying video information, which makes it possible to effectively detect and counteract enemy UAVs at a considerable distance. An algorithm of actions to be taken by law enforcement officers when using this complex is also developed and described. Proposals for creating a hardware and software system based on the complex with the possibility of spoofing a video stream are outlined.Conclusions. The results of the study indicate the need to supply law enforcement agencies with an identification system for detecting and suppressing UAVs having the ability to intercept an analog radio signal carrying video information. The use of such a system across a wide area subject to UAV attacks will significantly improve the effectiveness of alerting all categories of employees and civilians, as well as contributing to the establishment of airspace control and improving the effectiveness of the fight against UAVs.